Strengthening Early Childhood Education and Care in Luxembourg. - OECD. (Paris : Organization for Economic Cooperation & Development, 2022)
In supporting children's development, countries invest in the future successes of economies and societies. Awareness of the critical role early childhood education and care (ECEC) plays in setting a strong foundation for children's learning, development and well-being has grown among policy makers worldwide.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Early childhood education; Electronic books